Modeling forensic evidence systems using design science - Armstrong, Colin; Armstrong, Helen (Springer, 2010)
This paper presents an overview of the application of design science research to the tactical management of forensic evicence processing. The opening discussion addresses the application of design science techniques to specific socio-technical information systems research in regard to processing forensic evidence. The discussion then presents the current problems faced by those dealing with evidence and a conceptual meta-model for a unified approach to forensic evidence is developed. Any practical application of the suggested model would be predominantly law enforcement driven; evaluation of sections of the model has been carried out by law enforcement participants in several international jurisdictions.